Unusual objects in the root canal of deciduous teeth: A report of two cases - Holla, Goda (Medknow Publications Pvt Ltd, 2010)
Accidental foreign body ingestion or aspiration is a common problem in children. Children often have a habit of inserting objects into their mouth. Some of these objects can be accidentally ingested or even aspirated which can be frightening and a stressful experience. But the presence of foreign objects in the teeth are rare. The foreign objects in the teeth may act as a potential source of infection and pain. In most of the cases, children avoid informing their parents due to fear of punishment. This paper presents two cases of foreign objects embedded in the deciduous teeth. In both the cases, parents were not aware of foreign body ingestion by their children.